PENINGKATAN KETERAMPILAN BERPIKIR KREATIF MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) PADA SISWA KELAS X SMPN 1 GALESONG UTARA - Israwati Hamsar; Besse Qur’ani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research conducted is a class action research consisting of two cycles, each of which has been conducted twice a meeting. Each cycle consists of 4 stages, namely (1) action planning, (2) action implementation, (3) observation and (4) reflection. Data collection in this study was by conducting interviews, observations through observation sheets of creative thinking skills in students, teacher activity sheets in implementing learning using project-based learning models and documentation. The results showed that the application of the project-based learning model in class X workshop subjects was able to improve students' creative thinking skills. The increase can be seen in the results of data analysis of each meeting cycle. Cycle I the level of creative thinking skills occurred at 44.44%. Then experienced an increase in cycle II of 43%, so that the percentage value was 87.50%, so it can be concluded that the application of the project-based learning model is able to improve creative thinking skills as seen from the increase that has reached more than 75% or as many as 21 students were able to meet the researchers' success indicators.